2021
DOI: 10.3390/jcm11010072
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Artery Disease in Subjects with Type 2 Diabetes: Risk Factors and Biomarkers

Abstract: Carotid atherosclerosis (CA) and, especially, carotid artery stenosis (CAS), are associated with a high risk of cardiovascular events in subjects with type 2 diabetes (T2D). In this study, we aimed to identify risk factors and biomarkers of subclinical CA and CAS in T2D individuals. High-resolution ultrasonography of carotid arteries was performed in 389 patients. Ninety-five clinical parameters were evaluated, including diabetic complications and comorbidities; antihyperglycemic, hypolipidemic, and antihypert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 74 publications
(95 reference statements)
0
7
0
Order By: Relevance
“…Several previous reports observed greater atherosclerotic burden in the carotid arteries of patients with DKD than in diabetic patients with preserved renal function [32][33][34][35]. However, most of these studies were performed in non-Caucasians and none evaluated multiple indices of carotid atherosclerosis (i.e., cIMT, degree of stenosis and plaque thickness) [32][33][34][35]. Interestingly, prospective studies suggest that carotid atherosclerosis predicts, not only cardiovascular events, but also renal function decline in patients with DKD [36,37].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Several previous reports observed greater atherosclerotic burden in the carotid arteries of patients with DKD than in diabetic patients with preserved renal function [32][33][34][35]. However, most of these studies were performed in non-Caucasians and none evaluated multiple indices of carotid atherosclerosis (i.e., cIMT, degree of stenosis and plaque thickness) [32][33][34][35]. Interestingly, prospective studies suggest that carotid atherosclerosis predicts, not only cardiovascular events, but also renal function decline in patients with DKD [36,37].…”
Section: Discussionmentioning
confidence: 98%
“…Recently, sterol-O-acyltransferase-1, an enzyme that esterifies free cholesterol, the NLRP3 inflammasome pathway and the interleukin-33/ST2 pathway have also been implicated in the atherogenetic process in these patients [25][26][27][28][29][30][31]. Several previous reports observed greater atherosclerotic burden in the carotid arteries of patients with DKD than in diabetic patients with preserved renal function [32][33][34][35]. However, most of these studies were performed in non-Caucasians and none evaluated multiple indices of carotid atherosclerosis (i.e., cIMT, degree of stenosis and plaque thickness) [32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Tissue relaxin-2 mRNA levels are inversely correlated with MMP-2 in mild atherosclerosis and positively correlated with eNOS in moderate atherosclerosis, which supports the beneficial effect of relaxin-2 in this pathology [ 170 ]. Recently, Klimontov et al (2022) found no associations between serum levels of relaxin-2 and carotid atherosclerosis in patients with type 2 diabetes (T2D) [ 171 ]. A feasible explanation of these results could be that some confounders, such as insulin sensitivity, may modify the relationship between relaxin-2 and atherosclerosis in diabetes [ 171 ].…”
Section: Relaxin-2 As a Biomarker In Cardiovascular Diseasementioning
confidence: 99%
“…Recently, Klimontov et al (2022) found no associations between serum levels of relaxin-2 and carotid atherosclerosis in patients with type 2 diabetes (T2D) [ 171 ]. A feasible explanation of these results could be that some confounders, such as insulin sensitivity, may modify the relationship between relaxin-2 and atherosclerosis in diabetes [ 171 ].…”
Section: Relaxin-2 As a Biomarker In Cardiovascular Diseasementioning
confidence: 99%
“…Thus, they can notice subclinical carotid artery stenosis without developing a stroke or having an idea of the severity of the concomitant coronary artery disease. 24,25 In addition, interventional cardiologists who perform carotid artery stenting will more easily perform pre-and post-procedure followups of patients with carotid artery USG without the need for radiologists. 26,27 Performing carotid ultrasonography and echocardiography will increase time and labor intensity.…”
Section: Main Pointsmentioning
confidence: 99%